AB0374 Long-Term Safety in Rheumatoid Arthritis before and after Certolizumab Pegol Dose Increase/Decrease: Analysis of Data Pooled from the RAPID1 and RAPID2 Randomized Trials. (10th June 2014) - Haraoui, B.; Bykerk, V.P.; van Vollenhoven, R.; de Longueville, M.; Luijtens, K.; Ralston, P.; Kavanaugh, A.
Abstract : Background: Certolizumab pegol (CZP) is approved for adult patients (pts) with rheumatic diseases (RA, PsA and axSpA) at a maintenance dose of 200mg Q2W or 400mg Q4W. In RAPID1 1 (52 wks) and RAPID2 2 (24 wks) randomized clinical trials (RCTs [NCT00152386 and NCT00160602 ]), CZP treatment was given at a loading dose of 400mg at Wks 0, 2, and 4, followed by CZP 200mg Q2W, or at CZP 400mg Q2W in pts with active RA. All pts entering open-label extensions (OLEs [NCT00175877 3 and NCT00160641 4 ]) received CZP 400mg Q2W for ≥6 months. Results from the feeder studies revealed that the null hypothesis of no difference between doses could generally not be rejected. Consequently, dose was reduced to CZP 200mg Q2W for all pts. 3, 4 Objectives: To present safety data evaluating the potential effect of CZP dose change over 12 wks prior to and post dose-escalation or dose-reduction, in line with treat-to-target. Methods: Post-hoc analysis was performed on pooled RAPID1 and RAPID2 CZP data: 1) dose-escalation from CZP 200mg Q2W to CZP 400mg Q2W, 2) dose-reduction from CZP 400mg Q2W to CZP 200mg Q2W (Figure). Results: 557 pts randomized to CZP 200mg Q2W in the RCTs entered the OLEs, with dose-escalation to 400mg Q2W. Of these, 210 pts (37.7%) experienced an AE in the 12 wks prior to dose-escalation compared with 203 pts (36.4%) in the 12 wks post dose-escalation (Table). There were no confirmed cases of active tuberculosis (TB) in either period. 94.4% of AEs were mild-moderate: 65 and 71 pts, respectively, considered to be drug-related. The incidence of infections increased post dose-escalation but remained at a similar level during dose-reduction. Malignancies were reported in 3 pts during the 12 wks prior to (1 testis, 2 basal cell carcinoma [BCC]) and post (1 each of testis, lung and peritoneal) dose-escalation. During OLEs, 1110 pts received CZP 400mg Q2W for ≥6 months before dose-reduction. Of these, 365 pts (32.9%) experienced an AE in the 12 wks prior to dose-reduction, compared with 342 pts (30.8%) in the 12 wks post dose-reduction; 94.1% of AEs were mild-moderate: 102 and 91 pts, respectively, considered drug-related. Incidence of SAEs and infections was similar prior to and post dose-reduction. 2 pts reported malignancies in the 12 wks post dose-reduction (1 gastric, 1 BCC). There were no confirmed active TB cases in the 12 wks prior to dose-reduction and 2 cases in the 12 wks post dose-reduction. The number of AEs leading to withdrawals was low and no deaths were reported during the dose-escalation and dose-reduction study periods evaluated. Conclusions: Overall, despite a modest infection rate increase after dose-escalation, no new safety concerns emerged during dose-escalation or dose-reduction, and AE rates were generally similar between periods. However, the natural trend of a decreasing rate of AEs was observed over time, as is usual in RA clinical trials. References: Keystone E. Arthritis Rheum 2008;58:3319-3329. Smolen J.S. Ann Rheum Dis 2009;68:797-804. Keystone E. Ann Rheum Dis 2013; epub. Smolen J.S. Arthritis Rheum 2013;65:S988. Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: B. Haraoui Grant/research support: Abbott, Amgen, BMS, Janssen, Pfizer, Roche, UCB Pharma, Consultant for: Abbott, Amgen, BMS, Janssen, Pfizer, Roche, UCB Pharma, Speakers bureau: Abbott, Amgen, BMS, Janssen, Pfizer, Roche, UCB Pharma, V. Bykerk: None declared, R. van Vollenhoven Grant/research support: AbbVie, BMS, GSK, Pfizer, Roche, UCB Pharma, Consultant for: AbbVie, Biotest, BMS, GSK, Lilly, Merck, Pfizer, Roche, UCB Pharma, Vertex, M. de Longueville Employee of: UCB Pharma, K. Luijtens Employee of: UCB Pharma, P. Ralston Consultant for: UCB Pharma, A. Kavanaugh Grant/research support: Abbott, Amgen, BMS, Pfizer, Roche, Janssen, UCB Pharma DOI: 10.1136/annrheumdis-2014-eular.1763